Biological Treatments and Target Therapies for Pediatric Respiratory Medicine: Not Only Asthma - Ghirardo, Sergio; Mazzolai, Michele; Di Marco, Antonio; Petreschi, Francesca; Ullmann, Nicola; Ciofi degli Atti, Marta Lucia; Cutrera, Renato (Frontiers in Pediatrics, 2022)
We present a broad but obviously not an exhaustive description of biological and other target therapies in pediatric pneumology. The article starts with T2-High asthma and its current biological treatment and prescribing indications, focusing on the molecular rationale to propose a flow-chart to guide clinical choice. Molecular rationales of such treatments are used to introduce a more general description of the biological and molecular approach to target therapies' application. We introduce a general interpretation approach to neutrophilic asthma using this molecular plausibility approach. Thereafter, we suggest possible future therapies, mainly targeting interleukin-1 and interleukin-17. Indeed, cytokines can be excellent targets for several biological treatments. Downregulation of specific cytokines can be crucial in treating autoinflammatory and rheumatological diseases with pulmonary involvement. Such conditions, although rare, should be early recognized because they can present dramatic improvement with properly targeted therapy. We face these conditions in a cherry-picking fashion picturing SAVI, CANDLE, and COPA syndrome's pulmonary involvement. Such examples are functional to highlight the importance of molecular-based thinking for patients with rare conditions. Such an approach is even crucial for patients with no approved but possibly highly effective therapies. Due to the rarity of these conditions, we point out the concept of basket trials using the example of cytokinin-directed immunosuppressive treatment. Lastly, we give an example of augmentative therapy using the alpha1 antitrypsin deficiency as a model. In summary, the article presents a collection of the most recent achievements and some possible future developments in target therapies in pediatric pulmonology.